First report on sexually transmitted infections among trans (male to female transvestites, transsexuals, or transgender) and male sex workers in Argentina: high HIV, HPV, HBV, and syphilis prevalence - Dos Ramos Farías, María Sol (2011)
Fil: Dos Ramos Farías, María Sol. Universidad de Buenos Aires. Facultad de Medicina. Departamento de Microbiología, Parasitología e Inmunología. Centro Nacional de Referencia para el SIDA; Argentina.